From Red to Gray : The "Third Transition" of Aging Populations in Eastern Europe and the Former Soviet Union - Chawla, Mukesh; Betcherman, Gordon; Banerji, Arup (Washington, DC: World Bank, 2012)
This report focuses on the challenges that the region's aging countries will now face in having to deal with multiple transitions. It argues that their task ahead, though uniquely daunting, is by no means impossible. Indeed, many of the potential problems can be addressed through sensible and thoughtful policies that can be enacted over the next few years. The only danger likely lies in complacency, in not being proactive in addressing the challenges. This report finds, first, that some of the concerns about aging in Eastern European and Former Soviet countries are probably misplaced. Second, the analysis in the report validates concerns about future fiscal strains in some of the region's aging countries, but finds that many of the drivers of higher future public expenditures are unrelated to aging. This report is particularly focused on the future-a future in the region that is critically dependent on actions that countries and societies take now, and over the next few years. The report sends two central messages, which are analyzed against the different patterns of aging across the region. Red light to green light: Growing older does not have to mean growing slower. Aging is not a stop sign for growth-if countries enact policies that boost productivity and labor force participation. Red ink to black ink: Waging sensible policies can ease aging's spending impact. The policies needed to manage much of the expected jump in public spending-especially the impacts on pensions and on health care-are well known. They need only to be enacted and implemented.